An integrated psychological response score of the occupants based on their activities and the indoor environmental quality condition changes. (October 2017) - Kim, Jimin; Hong, Taehoon; Jeong, Jaemin; Koo, Choongwan; Kong, Minjin
Abstract: Psychological response based on the indoor environmental quality (IEQ) condition changes and activities of the occupants, can be assessed via indoor air quality (IAQ) satisfaction and thermal comfort. However, it is difficult to analyze both indices at the same time because they are measured on different scales. Therefore, this study aimed to develop an integrated psychological response score of the occupants based on 22 experimental participants' activities and the IEQ condition changes by using the weighted Euclidean distance. For this purpose, the experiment was designed with three scenarios to simulate the IEQ condition changes (i.e., CO2 concentration and operative temperature) during an 8-h working period. In each scenario, six cognitive tasks that simulate office work were performed to consider the activities of the occupants. A questionnaire survey on IAQ satisfaction and thermal comfort was conducted before and after (i) office work and (ii) IEQ condition changes. As a result, when the operative temperature was changed from 18.70 °C (cold) to 25 °C (neutral), the best psychological response score was calculated as 0.335. In addition, the occupants were more affected by the operative temperature than the CO2 concentration. It was shown that the mental health status based on IEQ condition, while considering both the indoor air pollutant and indoor climate, could be expressed as a single index. The mechanical system designer and facility manager can design or operate the IEQ condition considering the integrated psychological response score of the occupants, which can be used as an IEQ condition management guideline for mental health. Highlights: An integrated psychological response score of the occupants was developed. Thermal comfort was improved when the operative temperature was changed to neutral. Occupants in the office-work state cannot well recognize the IAQ condition. Best score was found when operative temperature was changed from cold to neutral. Occupants were affected by the indoor climate rather than the indoor air pollutant.